Clinical heterogeneity and reduced penetrance in DICER1 syndrome: a report of three families. Issue 6 (December 2021) - Azzollini, Jacopo; Ferrari, Andrea; Stracuzzi, Alessandra; Chiaravalli, Stefano; Terenziani, Monica; Spreafico, Filippo; Grasso, Maurizia; Collini, Paola; Pensotti, Valeria; Massimino, Maura; Arbustini, Eloisa; Manoukian, Siranoush
Introduction: DICER1 syndrome is characterized by increased susceptibility to malignancies, mostly occurring in childhood. The range of phenotypic effects of DICER1 variants is under investigation, and the syndrome's phenotypic spectrum is steadily widening. We report on three Italian families showing heterogeneous clinical presentation and reduced penetrance in family members. Case descriptions: Patient 1 is a 10-year-old girl with a Sertoli-Leydig cell tumor. Although family history was unremarkable, genetic testing identified a DICER1 germline variant, inherited from her healthy father. Benign thyroid nodules were subsequently diagnosed in both the proband and her father. Patient 2 is an 8-month-old boy with type 1 pleuropulmonary blastoma. His sister developed a nephroblastoma at age 2 years. A DICER1 novel variant was identified in both siblings and their healthy father. Patient 3 is a 22-year-old man who developed a spinal extramedullary intradural mass diagnosed as rhabdomyosarcoma with a peculiar tubular, gland-like component. Tumor testing revealed two pathogenic DICER1 variants, one of which was confirmed to be germline and identified in his 17-year-old healthy brother and in his father, who showed multiple thyroid nodules. Conclusions: Among our patients, three developed tumors most frequently associated with DICER1 syndrome (i.e. pleuropulmonary blastoma, nephroblastoma, and Sertoli-Leydig cell tumor). One developed a peculiar sarcoma of the spinal cord not previously described in DICER1 syndrome. Genetic testing in relatives highlighted the paternal origin and reduced penetrance in all families, with thyroid benign lesions as the most common features in otherwise unaffected individuals.